Pemodelan Aplikasi Pengadaan Barang Menggunakan Metode Waterfall - Arizka Anggraini; Latifa Khoirani; Armansyah Armansyah (Jurnal Sistem Informasi dan Ilmu Komputer, 2024)
Procurement is a recurring activity in a company's business process. While the traditional procurement process is often considered less efficient and effective, it requires a better solution. The traditional procurement process also often requires a long time, high cost, and lack of transparency. This can lead to inefficiency and the risk of misuse. This research aims to develop a more efficient and effective procurement application model using SDLC and waterfall methodologies. This research uses observation methods to study the current procurement process and interviews to get input from stakeholders regarding application needs. The results showed that the developed procurement application model can help companies in a more efficient and effective procurement process. This application model can help companies to save time and costs, as well as increase transparency and accountability of the procurement process.